2015
DOI: 10.18632/oncotarget.3481
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-derived stem cells promote tumor initiation and accelerate tumor growth by interleukin-6 production

Abstract: Adipose-derived stem cells (ADSCs) are multipotent cells that have attracted much recent attention. Here, we show that ADSCs enhance sphere formation and in vivo tumor initiation of breast and colon cancer cells. In co-culture, ADSCs induced several stem cell markers in cancer cells. ADSCs also accelerated tumor growth. Interaction of ADSCs and cancer cells stimulated secretion of interlukin-6 in ADSCs, which in turn acted in a paracrine manner on cancer cells to enhance their malignant properties. Interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 49 publications
2
59
1
1
Order By: Relevance
“…Indeed, recent studies have shown that ADSCs may play a vital role in cancer progression . Some clinical trials also indicated that ADSCs may provide a suitable microenvironment for BCC growth which increases the risks of recurrence and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have shown that ADSCs may play a vital role in cancer progression . Some clinical trials also indicated that ADSCs may provide a suitable microenvironment for BCC growth which increases the risks of recurrence and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…and exosomes and extra-cellular matrix components (MMP-11, collagen IV, etc.). [14][15][16][17] Peritumoral edema caused by the release of cytokines can also conduce to decrease the peritumoral fat proportion. Loss of the peritumoral fat content on IDEAL-IQ may reflect these pathological changes in the microenvironment of the breast.…”
Section: Discussionmentioning
confidence: 99%
“…The paracrine signaling effects of ASCs on colorectal cancer (CRC) have also been well described in the literature . Wei et al demonstrated that ASCs release the cytokine IL‐6 to act on CRC cells through the JAK2/STAT3 pathway to increase sphere generation and cell growth and upregulate self‐renewal gene expression .…”
Section: Ascs In Cancermentioning
confidence: 99%
“…Wei et al demonstrated that ASCs release the cytokine IL‐6 to act on CRC cells through the JAK2/STAT3 pathway to increase sphere generation and cell growth and upregulate self‐renewal gene expression . Furthermore, cancer cells promoted increased secretion of IL‐6 from ASCs . Li et al demonstrated that senescent ASCs have a more significant impact on CRC cell proliferation than nonsenescent ASCs .…”
Section: Ascs In Cancermentioning
confidence: 99%